ANALISIS PERENCANAAN PERPAJAKAN DAN BEBAN PAJAK TANGGUHAN BERDAMPAK TERHADAP MANAJEMEN LABA - Rizki, Nonon Dheriana; Mulyana, Asep; Sutrisna, Wawan Asad; Waruwu, Fotuho; Heryanto, Toto (Information Technology and Science (ITScience), 2025)
This study aims to influence tax planning and deferred tax expenses on earnings management in banking companies listed on the Indonesian stock exchange in the 2018-2022 period. the focus of this research is focused on the factors that influence earnings management, with the variables considered are tax planning and deferred tax expense. The research method used is quantitative and regression analysis, using financial report data from banking companies listed on the Indonesian stock exchange for the 2018-2022 period. Data is analyzed for the last five years period. The results of the analysis show that tax planning and deferred tax expenses have a simultaneous effect on earnings management Keywords: Profit Management ,Tax Planning, Tax Burde